2019
DOI: 10.3390/su12010263
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Generational Gap in the Hospitality Industry: Reverse Mentoring—An Innovative Talent Management Practice for Present and Future Generations of Employees

Abstract: In the present generational context, talent management approaches and practices have evolved from the stage of "war for talent", defined by competitiveness and elitism, to a more collaborative and inclusive "post-war stage". Innovative solutions are increasingly important. In this framework, the main aim of the paper is to confirm that reverse mentoring, a talent management practice which appeared as a response to the necessity to bridge the present generational gap, can be considered a valuable approach in ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 69 publications
(235 reference statements)
1
20
0
Order By: Relevance
“…A number of scholars have recommended that leadership is favorably associated with the business commitment and employee innovation in companies [33][34][35]. For example, constructive management approach could generate employee innovative solutions [36]. Research has also suggested that the improvement of a hotel organization's innovativeness could be positively affected by the capability of the leader to show the constructive behaviors [37].…”
Section: Constructive Leadership and Psychological Safety Of Employeesmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of scholars have recommended that leadership is favorably associated with the business commitment and employee innovation in companies [33][34][35]. For example, constructive management approach could generate employee innovative solutions [36]. Research has also suggested that the improvement of a hotel organization's innovativeness could be positively affected by the capability of the leader to show the constructive behaviors [37].…”
Section: Constructive Leadership and Psychological Safety Of Employeesmentioning
confidence: 99%
“…In addition, past studies on creativity and innovation in the hospitality field have generally counted on qualitative contexts and students for sampling [80][81][82]. That is, few studies have focused on employee innovative behaviors in the hospitality context [14,36]. Therefore, there has been a call for more studies to empirically explore the hypothesized relationships between creativity and innovation in the service industry [83].…”
Section: Evaluation Of the Findings And Theoretical Implicationsmentioning
confidence: 99%
“…Reverse mentoring is emerging as an innovative talent management practice, allowing for the bridging of skills, generational, digital and other workforce gaps. Romanian and Swiss hospitality industries experienced the challenge of a lack of trust by employees on whether managers can effectively implement reverse mentoring as a talent innovation strategy, where the younger generations teach and develop older employees on 4IR integration [13]. Today's dynamic business and 4IR environments require managers and employees to gain business agility and flexibility.…”
Section: Managing Talented Employees Via Talent Innovationmentioning
confidence: 99%
“…HR and line managers must negotiate, engage, nurture, mentor and coach employees at all levels. Reverse mentoring and coaching allows for younger generations to train, develop and transfer skills and competencies into older employees and vice versa [1,13,17]. HR has transformed to integrate technological systems and analytics in the 4IR landscape; thus becoming a key driver towards further transitioning.…”
Section: Drivers Of Hr and Human Capital Transitioningmentioning
confidence: 99%
See 1 more Smart Citation